Сказки советских писателей - Ханбеков Леонид Васильевич (Художественная литература, 1991)
Экземпляры: Ф-14 (20190520) / Инвентарный номер: 94020 / Цена: / Сис.шифр: 84(2=411.2)6-45 / Авт.знак: С 42 / ГРНТИ: 17.82.90 / ББК: 84(2=411.2)6-45